1998
DOI: 10.1177/107424849800300102
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Changes and Mortality Due to Myocardial Infarction in Rats With or Without Imidapril Treatment

Abstract: BACKGROUND: Various angiotensin-converting enzyme inhibitors are known to improve heart function and prolong survival in patients and animals after myocardial infarction. Because myocardial infarction is known to induce arrhythmias, this study tested the hypothesis that early treatment with the angiotensin converting enzyme inhibitor imidapril reduces mortality during acute myocardial infarction because of protective effects against arrhythmogenesis. METHODS AND RESULTS: Rats were randomly divided into four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…Three-lead (limb leads I, II, and III) electrocardiograms (ECGs) were recorded in experimental rats on days 1, 3, 7, and 21 after coronary occlusion (20). The control values were measured in all rats before occluding the coronary artery.…”
Section: Electrocardiogram Measurements and Infarct Size Determinationmentioning
confidence: 99%
“…Three-lead (limb leads I, II, and III) electrocardiograms (ECGs) were recorded in experimental rats on days 1, 3, 7, and 21 after coronary occlusion (20). The control values were measured in all rats before occluding the coronary artery.…”
Section: Electrocardiogram Measurements and Infarct Size Determinationmentioning
confidence: 99%
“…The selection of imidapril for this study was mainly due to the fact that this long‐acting ACE inhibitor has been reported to reduce mortality due to coronary artery disease in mice to a greater extent than other ACE inhibitors (Ogiku et al ., 1994). In addition, imidapril has been shown to reduce mortality and prevent subcellular remodeling in the MI rat model of CHF (Ren et al ., 1998; Tappia et al ., 1999; Wang et al ., 2002; 2003). Some experiments were also carried out to test if another ACE inhibitor, enalapril (Fujii et al ., 2002), and an AT 1 R blocker, losartan (Ruzicka et al ., 1999), produce effects similar to those seen with imidapril.…”
Section: Introductionmentioning
confidence: 99%
“…Since renin-angiotensin system (RAS) is known to play an important role in maintaining cardiovascular homeostasis and is considered to be involved in the pathophysiology of myocardial infarction (MI) [17], extensive efforts have been made to improve heart function in the infarcted animals with various RAS inhibitors. Treatment of rats with different angiotensin converting enzyme (ACE) inhibitors and angiotensin II receptor (AT1R) antagonists has been shown to prevent ventricular remodelling, improve heart function, change hormone profile and reduce mortality in the infarcted animals [18][19][20][21][22]. Although the cellular and molecular mechanisms by which these drugs improve cardiac function in heart failure have not yet been clearly defined, Shao et al [23] have demonstrated the effect of ACE inhibition on sarcoplasmic reticular gene expression whereas Wang et al [24] demonstrated that the beneficial effects on the failing heart are associated with prevention of changes in myosin heavy chain isozyme protein contents and gene expression.…”
Section: Introductionmentioning
confidence: 99%